2012
DOI: 10.1007/s10397-012-0759-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep rectovaginal endometriotic nodules: perioperative complications from a series of 3,298 patients operated on by the shaving technique

Abstract: The purpose of this study was to analyze complication and recurrence rates after deep endometriotic nodule surgery. A total of 3,298 cases of deep endometriotic nodules were analyzed. The shaving technique was used, avoiding bowel resection. Laparoscopic nodule resection was performed successfully in all cases. Major complications included: (1) rectal perforation in 42 cases (1.3 %), (2) ureteral retention (<5 days) in 21 cases (0.64 %), (3) ureteral injury in 10 cases (0.3 %), and (4) fecal peritonitis in 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 55 publications
(94 reference statements)
0
47
0
2
Order By: Relevance
“…Very similar data were found in a series of cases previously observed in our service 22 and in a large study with more than 3,000 operated women, which found 95% of dysmenorrhea and 87% of dyspareunia. 16 There is a wide range of drug options for symptom control; however, the decision to perform surgical treatment with resection of the endometriotic lesions proved to be the therapeutic option with better results in the control of symptoms and for quality of life. 23,24 In addition, a significant number of intestinal lesions have a fibrotic component that does not respond to hormonal suppression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very similar data were found in a series of cases previously observed in our service 22 and in a large study with more than 3,000 operated women, which found 95% of dysmenorrhea and 87% of dyspareunia. 16 There is a wide range of drug options for symptom control; however, the decision to perform surgical treatment with resection of the endometriotic lesions proved to be the therapeutic option with better results in the control of symptoms and for quality of life. 23,24 In addition, a significant number of intestinal lesions have a fibrotic component that does not respond to hormonal suppression.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques used to treat the intestinal lesions conformed to the criteria to try to avoid large intestinal resections, within the possibilities of the size of the lesion, while maintaining the radicality necessary to treat the symptomatic disease. 16,[27][28][29] In 44% of the cases, it was possible to carry out the excision of lesions by means of "shaving," precisely because those lesions restrict themselves to the more superficial muscular layer of the intestine. In 19% of the lesions with involvement beyond the muscular layer and up to 30 mm, a discoid resection of the rectum was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…До сих пор остается неясным, лимфатическое пора-жение при эндометриозе -это результат инвазивного процесса или регионального лимфатического оттока от эндометриоидных повреждений. Однако в литературе имеются доказательства того, что глубокий инфильтратив-ный эндометриоз может иметь признаки злокачественно-го процесса, а также вследствие лимфоваскулярной инвазии может происходить перенос эндометриоидных клеток в экстрагенитальные органы [18]. Радикальность удаления глубокого инфильтративного эндометриоза во время оперативного лечения значительно улучшает фер-тильность у таких больных и достоверно снижает риск возврата заболевания [19].…”
Section: результаты клинического и эндоскопического обсле-дования болunclassified
“…(32 больных), рецидив НГЭ диагностировался у 77,3% больных (n = 17) (p < 0,05). Помимо боли, анатомических искажений и хирургических осложнений спаечный процесс, по дан-ным ряда авторов, может также играть роль в развитии эндометриоидных кист яичников и глубокого инфильтра-тивного эндометриоза [16,18,20]. Таким образом, про-филактика образования спаек в послеоперационном периоде является одним из самых важных аспектов лече-ния эндометриоза.…”
Section: результаты клинического и эндоскопического обсле-дования болunclassified